DISRUPTION OF SUPPLY CHAIN IN NIGERIA CONSTRUCTION INDUSTRY AND ITS ATTENDANT CONSEQUENCES - Abah, Emmanuel; Oni, Olalere Simeon; Etim, Emmanuel Jeremiah (FUDMA JOURNAL OF SCIENCES, 2025)
The effective management of supply chain in Nigerian Construction Industry is a critical aspect of the country's economy. The study aims on evaluating the disruption of supply chain in Nigeria construction industry and its attendant consequences with a focus on Abuja, Nigeria.  Descriptive research design was used, the population of the study consisted of construction industry in Abuja which was randomly sampled. The instrument used for data collection was a researcher designed questionnaire. Data generated was analyzed using percentage, descriptive statistics of mean and standard deviation while the hypothesis was tested using linear regression with the aid of SPSS. The results of the study established that there is a low level of awareness of supply chain practices in Nigeria construction industry; Factors responsible for disruption of supply chain in Nigeria construction industry includes policy inconsistencies and Materials shortages is the attendant consequences for disruption of supply chain in Nigeria construction industry; Strategies for most effective supply chain in Nigeria construction industry includes technology integration; Awareness of supply chain practices in Nigeria construction industry have positive and significantly correlate on supply chain practices by Nigeria construction industry. It was recommended that more awareness on supply chain should be carried out in construction industry in Nigeria amongst others. The practical significance of the findings of this study is that it will help construction firms establish long-term partnerships with suppliers to mitigate risks associated with supply chain disruptions.
Keywords: Supply chain; Disruption; Consequences; Construction Industry